PRINSIP KEADILAN DALAM EKSEKUSI HAK TANGGUNGANMENURUT SISTEM HUKUM INDONESIA - Bachtiar Marbun (2022)
There are many conflicts over the Mortgage execution process due to the contradictory Mortgage Articles, the execution parate is regulated in Article 6, 14, 20 paragraph (1) of Law Number 4 of 1996, creditors have the right to make sales through auctions against debtors in default/default, Debtors object to being able to take legal action. Fiat execution is regulated in Article 26 of Law No.: 4 of 1996, thus creating legal uncertainty. The research in this thesis uses juridical normative research. The principle of justice in the execution of mortgages according to the Indonesian legal system, namely 1) Execution of mortgages is regulated in Article 6, 14 paragraph (2) and Article 20 of Law No.: 4 of 1996. Debtors who object to can fight then Article 224 HIR junto Law no. : 14 of 1970 Article 4 in conjunction with Law No.: 48 of 2009, is an unfair execution process based on Pancasila because it creates legal uncertainty, 2) Mortgage execution regulations Article 26 of Law No.: 4 of 1996, Regarding the procedure for implementing collateral confiscation, it is explained in Article 227 Paragraph (3) HIR. The procedure is subject to Articles 197, 198 and 199 HIR, these articles are the application of the principle of justice based on Pancasila because it finds justice and legal certainty.